Groundwater temperature evolution in the subsurface urban heat island of Cologne, Germany. Issue 6 (7th May 2014) - Zhu, Ke; Bayer, Peter; Grathwohl, Peter; Blum, Philipp
Abstract Long‐term heating of shallow urban aquifers is observed worldwide. Our measurements in the city of Cologne, Germany revealed that the groundwater temperatures found in the city centre are more than 5 K higher than the undisturbed background. To explore the role of groundwater flow for the development of subsurface urban heat islands, a numerical flow and heat transport model is set up, which describes the hydraulic conditions of Cologne and simulates the transient evolution of thermal anomalies in the urban ground. A main focus is on the influence of horizontal groundwater flow, groundwater recharge and trends in local ground warming. To examine heat transport in groundwater, a scenario consisting of a local hot spot with a length of 1 km of long‐term ground heating was set up in the centre of the city. Groundwater temperature‐depth profiles at upstream, central and downstream locations of this hot spot are inspected. The simulation results indicate that the main thermal transport mechanisms are long‐term vertical conductive heat input, horizontal advection and transverse dispersion. Groundwater recharge rates in the city are low (<100 mm a−1) and thus do not significantly contribute to heat transport into the urban aquifer. With groundwater flow, local vertical temperature profiles become very complex and are hard to interpret, if local flow conditions and heat sources are not thoroughly known. Copyright © 2014 John Wiley & Sons, Ltd.